Nomograms for the prediction of lateral lymph node metastasis in papillary thyroid carcinoma: Stratification by size - Feng, Jia-Wei; Ye, Jing; Hong, Li-Zhao; Hu, Jun; Wang, Fei; Liu, Sheng-Yong; Jiang, Yong; Qu, Zhen (Frontiers in Oncology, 2022)
Background: Lateral lymph node metastasis (LLNM) is a risk factor of poor prognosis in papillary thyroid cancer (PTC). We aimed to determine predictive factors and develop the nomograms for LLNM in patients with papillary thyroid microcarcinoma (PTMC) and macro-PTC. Methods: We reviewed medical records of 1106 patients that underwent surgery between January 2019 and January 2022. Patients were divided into PTMC and macro-PTC group. We developed preoperative and postoperative nomograms for predicting LLNM based on results of multivariate analysis. Internal calibration was performed for these models. Results: The number of metastatic lymph nodes in lateral compartment was higher in macro-PTC patients. LLNM was independently associated with gender, the number of foci, location, shape, and central lymph node metastasis (CLNM) in PTMC patients. For macro-PTC patients, chronic lymphocytic thyroiditis, the number of foci, location, margin, CLNM and central lymph node ratio were all independent predictors for LLNM. All above factors were incorporated into nomograms, which showed the perfect discriminative ability. Conclusion: The diameter of tumor has an impact on the rate of LLNM. Separate predictive systems should be used for PTMC and macro-PTC patients for more accurate clinical assessment of lateral lymph node status. Through these nomograms, we can not only detect high-risk patients with occult LLNM preoperatively, but also form appropriate treatment protocols for postoperative management of PTC patients with different risks.